ANALISIS PENGARUH FAKTOR KEMAMPUAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PENGANTAR POS KANTOR POS KELAS H SURABAYA - BAHRIBAHAR, 099913385 M (2001)
The purpose of this research is to know how far the effect of working competency factors toward the working productivity of postman of the Surabaya Post Office. Those working competency factors consists of knowledge, skill, and attitude, and the productivity factor is the amount of services (such as letter post, postal money orders, and giro service items) that handed by postman to the receiver. The technique of research is carried out through survey to the Surabaya Post Office, interview to Human Resources Manager and distribute 60 questioner to the postman as a respondent. The step of research, first, in order to look for the relationship among the three free variables of the working competency, that is knowledge, skill, and attitude toward the working productivity. The second, is to know the most dominant factor from the three research variable. The analysis of data is done by using multiple linear regression that is continued by processing data using SPSS computer programs. The hypothesis autentification apply simultaneous regression test ( F-test) and partial regression test (t-test). The research result of the reality level ct = 0,05 shows that first, the three free variable have essential effect toward working productivity of the postman that showed by the multiple determination coefficient grade (R) with contribution .180 (18,0%). The second, the knowledge variable give the most dominant effect on working productivity with r2 partial contribution .124 (12,41/o). The conclusion is, first, the three free variable use in this research has contribution 18,01/6 toward the working productivity of postman of the Surabaya Post Office. The second, the knowledge variable is the dominant variable showed with the grade r2 partial is 12,4%. This research is expected to be useful for manager of The Surabaya Post Office or outside manager as an input in the focus of information about effect factors to the postman working competency who work in the post office.